Options for managing chrysomelid leaf beetles in Australian eucalypt plantations: reducing the chemical footprint. (28th June 2013) - Elek, Jane; Wardlaw, Tim
Abstract In Australia, eucalypt plantations require management to prevent economic damage by native chrysomelid leaf beetles, generally by aerially spraying a broad‐spectrum insecticide. These beetles also pose a serious threat to plantations in other countries. Various alternatives, both 'landscape' and 'control' options, for managing leaf beetles were reviewed and evaluated by a panel of experts. Options were scored on effectiveness, feasibility for use, impact on the environment, perceived social acceptability (including by certification bodies) and perceived cost. None of the options were scored as well as broad‐spectrum insecticide for effectiveness, feasibility and perceived cost, although virtually all of the other options scored better for environmental and social outcomes. The highest ranked options were the 'landscape' option of tree improvement to reduce susceptibility to insect attack, and the 'control' option of attract‐and‐kill traps. The next three ranks were two 'landscape' options aimed at enhancing the effectiveness of natural enemy populations by conserving their overwintering sites and their alternative food and hosts, and then silvicultural management. The best strategy for an Integrated Pest Management programme would be a combination of 'landscape' options to reduce the frequency of pest outbreaks and, if outbreaks occur, spraying with biological insecticides until attract‐and‐kill traps become available, possibly in combination with repellent sprays in a push–pull strategy. If control measures fail to prevent damaging defoliation, plantations could be fertilized to encourage recovery. Because most of the alternative options are not yet available, many research directions were identified, with the highest priorities being to develop plantation stock that is less susceptible to defoliation and to develop attractants for leaf beetles.